A 10-year-old immunocompetent girl with endogenous fungal endophthalmitis: Report of a case and review of the literature. Issue 1 (January 2022) - Guerriero, Silvana; Dammacco, Rosanna; Albano, Valeria; Rizzo, Tiziana; Cassano, Flavio; Boscia, Francesco; Alessio, Giovanni
Endogenous Endophthalmitis (EE) is a rare cause of blindness in the pediatric age group and this may account for the paucity of management guidelines in the literature. In this report, we describe our experience with a 10-year-old immunocompetent female who developed EE and became blind because of rapidly progressive and destructive inflammatory changes in her eye in spite of seemingly timely treatment.